2016
DOI: 10.1111/jocn.13280
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care needs of patients with gynaecologic cancer

Abstract: Nurses trained in palliative care are needed to evaluate and meet cancer patients' needs regularly to improve quality of palliative care. Nurses should examine the underlying reasons for most prevalent problems and give nursing care accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Two recent Turkish studies reported on the needs of women with gynaecological cancer, revealing a high prevalence of symptoms and unmet palliative care needs (Akkuzu et al, 2018; Seven, Sahin, Yilmaz, & Akyuz, 2016). Akkuzu et al (2018) also identified that women required knowledge on pain management, daily living activities and psychological support.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent Turkish studies reported on the needs of women with gynaecological cancer, revealing a high prevalence of symptoms and unmet palliative care needs (Akkuzu et al, 2018; Seven, Sahin, Yilmaz, & Akyuz, 2016). Akkuzu et al (2018) also identified that women required knowledge on pain management, daily living activities and psychological support.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent Turkish studies also investigated the needs of women with gynaecological cancer using other tools. For example, the Three Levels of Needs Questionnaire (3LNQ) measured the intensity and burden of symptoms of 134 gynaecological cancer patients revealing a high prevalence of symptoms and unmet palliative care needs [ 15 ]. The second Turkish study from 2016 also reported the learning needs of 92 women with gynaecological cancer using the Patient Learning Needs Scale (PLNS) suggesting that women required knowledge on subjects such as pain management, daily living activities, and psychological support [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is emphasized in the literature that providing palliative care by a multidisciplinary team of specially trained nurses and healthcare workers is very important in terms of increasing the quality of life by meeting the need for effective care. 26,[29][30][31][32][33] In palliative care, it is emphasized that nurses must meet all physical and psychosocial needs of patients. 26,32,[34][35][36][37] In the study of Temelli 26 with nurses, it was determined that she expressed the ideal palliative care as providing psychological support and taking care of the patient with her loved ones painlessly, effectively, and happily.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, the fact that the majority of nurses agreed with the statement “the head of the palliative care team is a doctor” supports the previous study findings. However, it is emphasized in the literature that providing palliative care by a multidisciplinary team of specially trained nurses and healthcare workers is very important in terms of increasing the quality of life by meeting the need for effective care 26,29–33 …”
Section: Discussionmentioning
confidence: 99%